Stability and Adaptability Analysis of BRRI Developed Aus Varieties in Different Locations of Bangladesh (Bangladesh Rice Journal, 2019)
The genotype by environment (G×E) interactions can be observed by differential genotypic responses to varied environmental conditions. Its effect is to limit the accuracy of yield estimates and complicate the identification of specific genotypes for specific environments. The frequently used model additive main effects and multiplicative interaction (AMMI) were used in this study to identify high yielding Aus rice varieties having wide adaptation and or specific adaptation to environment. Multi environment trials on eight Aus rice varieties were conducted at four environmental conditions in 2016. Genotype by environment (G×E) interactions contribution was much higher than the genotypic effect and environmental effect on grain yield. The genotypes BRRI dhan65, BRRI dhan48 and BRRI dhan43 display higher adaptability and stability. Therefore they are included in the study and recommended to be used in all environments. The variety BRRI dhan65 was identified as the most suitable variety with wider adaptability in the region Kushtia followed by BRRI dhan48 and BRRI dhan43. Latest varieties performed better than the oldest ones based on grain yield and could be replaced through ensuring the supply chain of new promising varieties of that locality.Bangladesh Rice j. 2018, 22(1): 65-72